2012
DOI: 10.1073/pnas.1119578109
|View full text |Cite
|
Sign up to set email alerts
|

Coherent angular motion in the establishment of multicellular architecture of glandular tissues

Abstract: Glandular tissues form ducts (tubes) and acini (spheres) in multicellular organisms. This process is best demonstrated in the organization of the ductal tree of the mammary gland and in 3D models of morphogenesis in culture. Here, we asked a fundamental question: How do single adult epithelial cells generate polarized acini when placed in a surrogate basement membrane 3D gel? Using human breast epithelial cells from either reduction mammoplasty or nonmalignant breast cell lines, we observed a unique cellular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
164
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(191 citation statements)
references
References 50 publications
24
164
1
Order By: Relevance
“…Whereas our observation is consistent with recent studies on rotational motions (23,24), we find an unexpected role for rotational motion during assembly of basement membrane matrix. Interestingly, assembly of fibronectin matrix did not require the rotational motion.…”
Section: Discussionsupporting
confidence: 42%
“…Whereas our observation is consistent with recent studies on rotational motions (23,24), we find an unexpected role for rotational motion during assembly of basement membrane matrix. Interestingly, assembly of fibronectin matrix did not require the rotational motion.…”
Section: Discussionsupporting
confidence: 42%
“…We have previously reported that single keratinocytes can create helical tunnels in fibrin matrix (Ronfard and Barrandon, 2001), which might be related with the rotational motion in two-dimensional culture. Mammary epithelial cells also exhibit rotational motion (Kino-oka et al, 2004), which is required for sphere formation in three-dimensional culture (Tanner et al, 2012). In mammalian epidermis, keratinocyte stem cells are located in the basal layer of the interfollicular epidermis and epidermal appendages (Rochat et al, 1994; Jones in ITGA6, but not control shRNA-transduced two-cell colonies (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…26,35 The plasticity of the neoplastic phenotype and its normalization by induction of proper tissue organization has been reported multiple times bringing into question the existence of a neoplastic identity at the cellular level. 41,42 In this context, it is likely that the addition of normal stromal cells and myoepithelial cells would incrementally contribute to a more anatomically and functionally normal phenotype, whereas the addition of cancer-associated fibroblasts would produce fiber density maps on merged SHG and two-photon excited fluorescence channels, (C) form factor of epithelial structures, and (D) standard deviation of fiber density. *, statistical significance.…”
Section: Discussionmentioning
confidence: 99%